Visual Analysis of Trajectories in Multi‐Dimensional State Spaces. (27th May 2014) - Grottel, S.; Heinrich, J.; Weiskopf, D.; Gumhold, S.
<x xml:space="preserve">Abstract</x> Multi‐dimensional data originate from many different sources and are relevant for many applications. One specific sub‐type of such data is continuous trajectory data in multi‐dimensional state spaces of complex systems. We adapt the concept of spatially continuous scatterplots and spatially continuous parallel coordinate plots to such trajectory data, leading to continuous‐time scatterplots and continuous‐time parallel coordinates. Together with a temporal heat map representation, we design coordinated views for visual analysis and interactive exploration. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>